Sports and the Fight Against Corruption: The Need for Transparency in Indonesian Sporting Events (Indonesian Sports Justice Review, 2024)
Corruption within the sports industry can undermine the integrity of athletic competitions, perpetuate inequality, and distort the intended goals of sports development. This paper investigates the prevalence of corruption in Indonesian sporting events and explores the role of transparency in addressing these issues. Through an examination of key scandals, including bribery in event management, match-fixing, and the misallocation of funding, the study highlights the detrimental effects of corruption on public trust, athlete performance, and the broader sports ecosystem. Drawing from interviews with sports officials, athletes, and anti-corruption experts, the paper proposes reforms to improve transparency, such as stronger regulatory bodies, independent auditing of sports organizations, and increased public oversight. It concludes with a call for a cultural shift toward integrity and accountability in Indonesian sports governance.